Getting Universities to Adopt Corporate Governance - Not as Easy as It Looks! - Ansari, Khawar (World Bank, Washington, DC, 2012)
The main goal of International Finance Corporation's (IFC's) Corporate Governance Project in Pakistan is to establish sustainable capacity in the country so that, once the project is over, institutions will be able to improve their corporate governance practices to international standards using locally available resources. The project aims to achieve this goal by helping set up a stable and robust regulatory framework, establishing sustainable institutions to train directors and improve board performance, training the media in selecting and reporting issues that communicate the local relevance of corporate governance, and encouraging business schools to incorporate corporate governance as a core subject in the MBA curriculum.